Use of Electronic Corpora in Grammar Teaching: Acquisition of Frequent Lexical Bundles at Higher Levels of Learning - Rađenović, Anka М. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The modern approach to teaching grammar at higher levels of language proficiency is a combination of grammar and vocabulary in which a special place is occupied by the mastery of non-native speakers with frequent lexical bundles (collocations). The acquisition of frequent lexical bundles, since they are not generated through knowledge of rules or formulae, is the topic of a study on the acquisition of foreign languages, especially at higher levels of proficiency. Textbooks, dictionaries and grammars as the main source of information for students and teachers of foreign languages are insufficient tools for mastering frequent lexical bundles. For this reason, electronic corpora as sets of authentic texts represent a valuable resource for teachers and students in the process of teaching and learning a foreign language. Taking into account the specificity of the lexical-grammatical approach in the acquisition of modern Greek at higher levels of proficiency, the paper presents one of the possible approaches to the acquisition of frequent lexical bundles in grammar teaching by the use of electronic language corpora. The use of electronic corpora in grammar teaching at the university level can have implications both in the didactics of foreign languages and in the creation of curricula.
Keywords: electronic corpora; grammar teaching; frequent lexical bundles; modern Greek as L2; higher levels of language proficiency